2018
DOI: 10.1111/acel.12748
|View full text |Cite
|
Sign up to set email alerts
|

Vascular smooth muscle cells direct extracellular dysregulation in aortic stiffening of hypertensive rats

Abstract: SummaryAortic stiffening is an independent risk factor that underlies cardiovascular morbidity in the elderly. We have previously shown that intrinsic mechanical properties of vascular smooth muscle cells (VSMCs) play a key role in aortic stiffening in both aging and hypertension. Here, we test the hypothesis that VSMCs also contribute to aortic stiffening through their extracellular effects. Aortic stiffening was confirmed in spontaneously hypertensive rats (SHRs) vs. Wistar‐Kyoto (WKY) rats in vivo by echoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 36 publications
4
37
0
Order By: Relevance
“…Recent studies strongly suggest that stiff vascular vessels in aging-related arterial stiffening and atherosclerotic plaques promote monocyte adhesion and, subsequently, the progression of atherosclerosis [13,14]. We confirmed that human aortic endothelial cells enhance the formation of focal adhesion and stress fibers ( Figure S2), leading to cellular stiffening in response to LPS stimulation, as has similarly been observed with HUVECs.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Recent studies strongly suggest that stiff vascular vessels in aging-related arterial stiffening and atherosclerotic plaques promote monocyte adhesion and, subsequently, the progression of atherosclerosis [13,14]. We confirmed that human aortic endothelial cells enhance the formation of focal adhesion and stress fibers ( Figure S2), leading to cellular stiffening in response to LPS stimulation, as has similarly been observed with HUVECs.…”
Section: Discussionsupporting
confidence: 87%
“…Vascular stiffness has been primarily determined by the reconstitution of extracellular matrix components, fibrosis, and calcification in vascular vessels [12]. In addition, the increased stiffness of vascular smooth muscle cells and endothelial cells has similarly been observed in aging-related arterial stiffening and atherosclerotic plaques, respectively [13,14]. Our recent studies have also shown that endothelial cells increase their stiffness in response to proinflammatory stimuli [15].…”
Section: Introductionmentioning
confidence: 83%
“…In addition, some in vitro and in vivo animal studies have shown that some drug compounds have been found to be effective in the treatment of pathological conditions related to the upregulation of SRF. For example, a group of small-molecule inhibitors of RhoA transcriptional signaling (CCG-100602, CCG-203971, CCG-1423, CCG222740, and CCG222740) has been found to be able to inhibit MRTF/SRF-mediated upregulation of the gene transcription caused by several environmental (mechanical stress) and cytokine (TGF-b) stimuli and repressed fibrosis and ECM stiffness as well as the VSMC stiffness [37,79,81,[85][86][87][88][89]. Although the results remain contradictory and the mechanisms involved are still not fully identified, they provide a promising strategy for the development of a therapeutic drug for clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also established a link between upregulation of SRF/myocardin pathways and the pathogenesis of aortic stiffness in age-related hypertension [37,[79][80][81]. Aortic stiffness is known as an independent risk factor for hypertension and cardiovascular morbidity in the elderly, and it is associated with intrinsic mechanical properties of VSMCs [79]. The underlying molecular mechanisms contributing to this condition is not known.…”
mentioning
confidence: 99%
See 1 more Smart Citation